A Review on Cassava Residues as Adsorbents for Removal of Organic and Inorganic Contaminants in Water and Wastewater - Vasu Gajendiran; Prabu Deivasigamani; Selvaraju Sivamani; Ponnurengam Malliappan Sivakumar (Journal of Chemistry)
An increase in water demand for drinking, agriculture, and industries necessitates the treatment of water and wastewater. Among various conventional treatment techniques available, adsorption is found to be one of the most economical and feasible methods. Adsorbents from plant biomass are effective for the removal of organic and inorganic pollutants. Cassava has gained attention among researchers during the past decades due to its plentiful availability and resilient characteristics. Even though cassava contains cyanogenic glucosides as toxins, it is used in industries for development of various products. Cassava stem, rhizome, peel, and bagasse are industrial residues that are generated in abundance. The present review focusses on factors affecting adsorption using cassava residues, adsorbent preparation and activation methods, equilibrium, mass transfer, kinetics, and thermodynamic studies of adsorption.